2016
DOI: 10.1093/annonc/mdw364.34
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prognostic role of a 94-single nucleotide polymorphisms risk score in early breast cancer in the SIGNAL/PHARE prospective cohort: no correlation with clinico-pathological characteristics and outcomes

Abstract: Background: Genome-wide association studies (GWAS) have to date identified 94 genetic variants (single nucleotide polymorphisms (SNPs)) associated with risk of developing breast cancer. A score based on the combined effect of the 94 risk alleles can be calculated to measure the global risk of breast cancer. We aimed to test the hypothesis that the 94-SNP-based risk score is associated with clinico-pathological characteristics, breast cancer subtypes and outcomes in early breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similarly, two studies reported that a high PRS was associated with more favorable tumor characteristics including lowergrade ER-positive breast cancer, smaller size tumor, and less likely to be diagnosed with distant metastasis [45,53]. However, these findings have not always been consistently replicated in other studies [54].…”
Section: Polygenic Risk and Breast Cancer Classificationmentioning
confidence: 98%
“…Similarly, two studies reported that a high PRS was associated with more favorable tumor characteristics including lowergrade ER-positive breast cancer, smaller size tumor, and less likely to be diagnosed with distant metastasis [45,53]. However, these findings have not always been consistently replicated in other studies [54].…”
Section: Polygenic Risk and Breast Cancer Classificationmentioning
confidence: 98%
“…The OR-GRS was calculated in the same way as DL-GRS, but the sources of weight (log(OR)) were different. The OR were usually derived from meta-analysis or genomewide association studies (30)(31)(32)(33) , that is, it relied on external data rather than original data. Similarly, The EV-GRS method also relied on external data (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a heterogeneous and polygenic disease, and breast cancer susceptibility SNPs and genes are closely related to molecular subtype and clinical phenotypes (8)(9)(10). However, for many SNPs, evidence of an association with cancer is often weak, and accurate estimates of the cancer risks associated with variants are often not available (11).…”
Section: Introductionmentioning
confidence: 99%